ASSESSMENT OF CHANGES IN PAIN INTENSITY AND FUNCTIONAL MOBILITY IN PATIENTS WITH KNEE OSTEOARTHRITIS TREATED AT CUA DONG GENERAL HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To assess changes in pain intensity and functional mobility in patients with knee osteoarthritis treated at the Department of Traditional Medicine and Rehabilitation, Cua Dong General Hospital. Subjects and Methods: A prospective before–after observational study was conducted on 100 patients with knee osteoarthritis from January to June 2024. Pain and functional status were assessed using the VAS and Lequesne index before and after 10 days of treatment. Statistical analysis was performed using paired t-test, with p < 0.05 considered statistically significant. Results: The mean age of patients was 69.5 ± 13 years; females accounted for 53.0%, manual laborers 57.0%, disease duration from 1–5 years 48.0%, and grade I knee osteoarthritis 46.0%. A total of 98.0% of patients received combined treatment with modern medicine and traditional medicine. The VAS score decreased from 5.28 ± 1.02 to 2.20 ± 0.96 (p < 0.01). The Lequesne index decreased from 12.71 ± 5.0 to 5.88 ± 4.06 (p < 0.01). Conclusion: After 10 days of treatment at the department, there was a statistically significant improvement in pain intensity and functional mobility in patients with knee osteoarthritis.
Keywords: Knee osteoarthritis, Visual Analog Scale, Lequesne index, Traditional medicine, Rehabilitation.